Surgical management of vision loss in cerebral venous thrombosis: Case series from a tertiary care stroke center - Taallapalli Ashok Vardhan Reddy; Doniparthi V Seshagiri; Haripriya Krishna Reddy; Ameya A Patwardhan; Tarachand H Joshi; Dhaval Shukla; Girish B Kulkarni; Veerendra Kumar Mustare; Subasree Ramakrishnan (Annals of Indian Academy of Neurology, 2023)
Background and Purpose: Cerebral venous thrombosis (CVT) presenting as vision loss is uncommon. Raised intracranial tension in CVT is proposed as one of the mechanisms (13.2%). There are still unknown underlying mechanisms to explain vision loss in CVT. The safety and outcome of the surgery (optic nerve sheath fenestration [ONSF] or theco-peritoneal shunt [TPS]) to reduce intracranial hypertension and prevent vision loss has not been studied. Methods: A retrospective case record review of CVT patients with impending vision loss who underwent ONSF/TPS from 2007 to 2019 was performed from the stroke registry. All patients had formal neuro-ophthalmological evaluation and documentation of visual acuity, supplemented by visual field assessments by perimetry in a subset of patients. Safety and outcomes were assessed based on vision improvement and adverse effects after the surgery. Results: Among approximately 1400 patients with CVT admitted in the stroke ward over 12 years, surgery for rescuing vision was done in 18. Among these, the males were 6, and the females were 12. The mean age of presentation was 24 (range 18–52 years). All of them had headaches and progressive blurring of vision with papilledema. The number of patients who underwent TPS was 13, ONSF was 1, and both were 4. In the TPS group (26 eyes), vision improved in 15 eyes (57.7%), remained status-quo in 8 eyes (30.7%), and worsened in 3 eyes (11.5%). Four patients underwent both surgeries; three eyes improved, two remained status quo, and three worsened. One patient underwent ONSF, and his vision remained status quo (no perception of light). Three patients (17.6%) of the TPS group had minor complications (low-pressure headache, subdural hygroma), and five (29.4%) had major complications like subdural hemorrhage, abdominal wound infection, and meningitis. Conclusion and Implications: In patients with CVT, adequate vision monitoring is mandatory. Shunt surgeries (especially TPS) may help in stabilizing/improving vision in CVT patients with impending vision loss, despite adequate anti-edema measures (53.8% improved). Early diagnosis and precise decisions in referring for surgery are crucial.